The need of professional social support of the families undergoing divorce - Kaušylienė, Angelė; Cikatavičienė, Žaneta; Leliūgienė, Irena (Social Welfare: Interdisciplinary Approach, 2015)
The article is based on the results of qualitative research on the importance of professional social support for the family that experienced divorce. The research participants were as follows: preschool children of N city attending social care day centre and parents (6 couples), who after undergoing the divorce had the need for social support provided by professional caseworkers. The research uses qualitative research method applied to survey with four persons that had undergone the divorce recently. The research has revealed that the major demand of these parents with preteen children was the necessity of professional educational, psychological, medical, legal, mediatory support as well as consultancies. The informants had obtained support on institutional level, which was provided during divorce by personnel of Family Practice Institute and Initial Healthcare and Mental Health Centres as well as caseworkers of the municipalities. The research has demonstrated that a family undergoing divorce is lacking successive and complex help.
Keywords: divorce; social support; caseworker and family